Advanced separation of soluble organic matter in a low-rank coal and evaluation using unsupervised analyses. (15th November 2022) - Xu, Yang-Yang; Fan, Xing; Mo, Wen-Long; Muhammad, Turghun; Bai, Xiang; Saikia, Binoy K.; Wei, Xian-Yong; Ma, Feng-Yun
Highlights: Preparative HPLC separated and enriched soluble organic matter in coal. Three times of compounds were identified after the pre-separation. Molecular polarity and alkyl chain structure of analyte determine elution time. Unsupervised analysis methods follow different clustering principles. Abstract: Three soluble fractions (SFs) of a low-rank coal were obtained by sequential thermal dissolution (TD) using cyclohexane, toluene and methanol as the solvent. SFs were further separated using preparative high-performance liquid chromatography (HPLC) to obtain subfractions. Both SFs and subfractions were characterized by gas chromatography/mass spectrometry (GC/MS). Low polar compounds such as alkanes and arenes were enriched by cyclohexane. A large number of arenes and esters were detected in toluene extracts. Strong polar compounds like phenols were concentrated by methanol. After the separation by using preparative HPLC, more phenols, alcohols, esters and ketones were identified in subfractions, and the number of compounds detected by GC/MS increased by around 3 times. In addition, two trace compounds, (2, 6-dimethoxybenzoyl chloride and tetrachloro-o-benzoquinone), were identified and one compound, 1, 4-benzene-dicarboxylic acid-bis(2-ethylhexyl) ester, was enriched to 89.9% after separation. Two unsupervised analysis methods, hierarchical cluster analysis and principal components analysis, revealed the differences in distributional and compositional features of SFs and subfractions.